Evolution of Cataclysmic Variables with Binary-driven Mass Loss during Nova Eruptions - Tang, Wen-Shi; Li, Xiang-Dong; Cui, Zhe (The Astrophysical journal, 2024)
The discrepancies between observations and theoretical predictions of cataclysmic variables (CVs) suggest that there exists unknown angular-momentum-loss mechanism(s) besides magnetic braking and gravitational radiation. Mass loss due to nova eruptions belongs to the most likely candidates. While standard theory assumes that mass is lost in the form of radiation-driven, optically thick wind (fast wind), recent numerical simulations indicate that most of the mass loss is initiated and shaped by binary interaction. We explore the effect of this binary-driven mass loss (BDML) on the CV evolutions assuming a major fraction of the lost mass leaves the system from the outer Lagrangian point. Different from the traditional continuous wind picture, we consider the mass loss process to be instantaneous because the duration of nova eruptions is much shorter than the binary evolutionary timescale. Our detailed binary evolution calculations reveal the following results. (1) BDML seems able to provide extra angular momentum loss below the period gap. The mass transfer rates at a given orbital period occupy a large range, in agreement with the observed secular mass transfer rate distribution in CVs. (2) The enhanced mass transfer rates do not lead to a runaway mass transfer process and allow the white dwarfs to grow mass ≲0.1 M ☉ . (3) BDML can cause both positive and negative variations in the orbital period induced by nova eruptions, in line with observations, and can potentially explain the properties of some peculiar supersoft X-ray sources likely CAL 87, 1E 0035.4−7230, and RX J0537.7−7034.